PENERAPAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DENGAN MEDIA VISUAL DALAM PENINGKATAN HASIL BELAJAR IPS PADA SISWA KELAS IV SDN 1 BRECONG TAHUN AJARAN 2015/201 - Hidayatii, Nurul (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Teams Games Tournament (TGT) Model Using Visual Media in Improving Social Science Learning for the Fifth Grade Students of SD Negeri 1 Brecongin the Academic Year of 2015/2016.The objectiveof this research isto improve social science learning about technology development through the application of Teams Games Tournament (TGT) for the fourth grade students of SD Negeri 1 Brecong in the academic year of 2015/2016.This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection.Subjects of the research were 35 students of fourth grade students in SD Negeri 1 Brecong.The results of this research show thatthe application ofTeams Games Tournament (TGT) using visual media can improve social science learning for the fourth grade students of SDN 1 Brecong in academic year of 2015/2016.Keywords: Teams Games Tournament (TGT), visual media, social scienceAbstrak: Penerapan Model Kooperatif Tipe Teams Games Tournament (TGT) dengan Media Visual dalamPeningkatanHasil Belajar IPS padaSiswaKelasIV SDN 1Brecong TahunAjaran 2015/2016. Tujuan dari penelitian ini adalahmeningkatkan hasil belajar IPS tentang perkembangan teknologi melalui model kooperatif tipe Teams Games Tournament (TGT) dengan media visual pada siswa kelas IV SDN 1 Brecong tahun ajaran 2015/2016.Penelitian ini dilaksanakandalamtiga siklus terdiri dari perencanaan, pelaksanaan, pengamatan dan refleksi. Subjek penelitian ini adalah siswa kelas IV SDN 1 Brecongyang berjumlah 35 siswa. Hasil penelitian ini menunjukkan bahwa penerapan model kooperatif tipe Teams Games Tournament (TGT) dengan media visual dapat meningkatkan hasil belajar IPS pada siswa kelas IV SDN 1 Brecong tahun ajaran 2015/2016. Kata Kunci: Teams Games Tournament (TGT), Media Visual, IPS